Comparative Analysis of Some Methods of Measuring the Total Body Fat - Nawarycz, Tadeusz; Jankowski, Jerzy; Baszczyński, Jan; Nawarycz-Ostrowska, Lidia; Kajdos, Zdzisław (Anthropological Review, 1996)
The objective of this study was the comparison of three different methods: skin fold thikness, near infrared spectrophotometry and bioelectrical impedance for estimation of the total body fat. The measurements were made on the sample of 48 young men, 18-20 years old. The results turned out to be independent of the method which was used for estimation of the total body fat.